Toolkit to promote Paediatric Critical Care staff well-being: a report - Subramanian, G; Austin, D; Duncan, I; Donnelly, P; Butcher, I (Springer International Publishing, 2025)
Staff working in Paediatric Critical Care globally face many challenges. There has been a plethora of research conducted internationally indicating that staff working in these settings utilise a range of strategies to keep well. The Paediatric Critical Care Society in United Kingdom has created a well-being toolkit for all staff working in paediatric critical care settings both nationally and internationally. This toolkit is novel with ‘lived examples’ from units across the United Kingdom. The aim of this toolkit is to encourage well-being and normalise well-being discussions in Paediatric Critical Care. The toolkit whilst not an intervention, clearly outlines ten aspects of well-being that are crucial to ensuring that staff working on Paediatric Critical Care remain well. These include but are not limited to; spiritual, safety, psychological, environment, leadership, values and priorities and basic needs. Whilst the authors recognise the size of units internationally varies, these key aspects of well-being do not differ and are applicable to any unit. The authors envisage this toolkit as a resource that units can use for implementation of their well-being ambition and practices in an unexacting way.